HISTORY OF MANAGEMENT THOUGHT AND WERNER SOMBART - A. Kuzmichev (Управленческие науки, 2015)
Courses on the history of management thought became integral part of the educational process in Russian universities. However, among the classics of management thought there is still no worthy tribute to prominent scientist of the twentieth century Werner Sombart. His work, devoted to scientific management, is introduced into scientific circulation for the first time. There he gives a definition of scientific management, describes the principles of science, describes the emergence and development of science thought in Europe. Principles of management, according to Sombart, may relate to the enterprise as a whole (to the problem of the combination of all factors of production into one effective whole); apply only to the individual functions of the enterprise (calculation, loading and unloading of raw materials, etc.); relate to the use of capital (accounting or production processes), or „to have” as its object handling things (machine system) or human resources (wage system).Special place is given to the emergence of a new type of worker - the „industrial engineer” or „rationalization expert”. Sombart says, that „on all of these stages of labour” „continuous account of economic value of innovations for the enterprise economic interests” depends on industrial engineer. Engineer should promote discoveries and future innovations. Sombart believes that company’s scientific management makes further progress, when there are„engineers”, not only „overseer of the material process, but also required to take care of systematic relationships of the other production processes and of rational organization of human labor”.In the book much attention is devoted to bibliography in German, English and French on various aspects of management. Sombart’s approach to description of systems „on which enterprise is based” deserves much attention. The author distinguishes three systems: the standard system (management system), the number system (reporting system) and the tools system (the system of machines).